Peran Kiai Iskandar Umar Abdullatif di Krian Sidoarjo - Muhammad Akbar Firdaus (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2021)
Abstract: This study seeks to explore the autobiography of a character, namely Kiai Iskandar Umar Abdullatif in shaping the morals of the Krian community, Sidoarjo, the period 1985-2010. Society has a collective character that can be formed or changed to become more mature—in the assumption that some people are